2013
DOI: 10.1007/s10817-013-9286-5
|View full text |Cite
|
Sign up to set email alerts
|

Premise Selection for Mathematics by Corpus Analysis and Kernel Methods

Abstract: Smart premise selection is essential when using automated reasoning as a tool for large-theory formal proof development. A good method for premise selection in complex mathematical libraries is the application of machine learning to large corpora of proofs. This work develops learning-based premise selection in two ways. First, a newly available minimal dependency analysis of existing high-level formal mathematical proofs is used to build a large knowledge base of proof dependencies, providing precise data for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 33 publications
0
109
0
Order By: Relevance
“…Premise selection in large theories seems to be an important instance of the general proof guidance problem. It has been shown that proper design and choice of knowledge selection heuristics can change the overall success of large-theory ATP techniques by tens of percents [1]. This paper continues our work on machine learning algorithms for premise selection [1,5].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Premise selection in large theories seems to be an important instance of the general proof guidance problem. It has been shown that proper design and choice of knowledge selection heuristics can change the overall success of large-theory ATP techniques by tens of percents [1]. This paper continues our work on machine learning algorithms for premise selection [1,5].…”
Section: Introductionmentioning
confidence: 63%
“…It has been shown that proper design and choice of knowledge selection heuristics can change the overall success of large-theory ATP techniques by tens of percents [1]. This paper continues our work on machine learning algorithms for premise selection [1,5]. We investigate how the knowledge of different proofs can be integrated in the machine learning algorithms for premise selection, and how it influences the performance of the ATPs.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations